Analyzing current and future direction of non-oil primary balance: Case Study of Iraq Using Exponential Smoothing model - محمد مهند عزيز; سعيد عدلة عبد الله (Journal of Economics and Administrative Sciences, 2019)
In recent years, non-oil primary balance indicator has been given considerable financial important in rentier state. It highly depends on this indicator to afford a clear and proper picture of public finance situation in term of appropriate and sustainability in these countries, due to it excludes the effect of oil- rental from compound of financial accounts which provide sufficient information to economic policy makers of how economy is able to create potential added value and then changes by eliminating one sided shades of economy. In Iraq, since, 2004, the deficit in value of this indicator has increased, due to almost complete dependence on the revenues of the oil to finance the budget and the obvious decline of the non-oil sectors contribution in the economy. By using Exponential Smoothing method for predicting the role of this indicator till 2025, It has been shown that the trend of this indicator will rise with the assumption that Iraq’s economic and financial policy remains essentially unchanged. This research recommends, policy maker should adopt economy policy that reduce the non-oil deficit by 3% annually and allocating part of the oil revenues to support strategic projects in another sectors.